Development of strategy formulation with scenario planning approach case study on Zakat House - Ali Mujianto; Siska Noviaristanti (Goodwood Publishing, 2025)
Purpose: This study aims to provide strategic solutions for Rumah Zakat over the next ten years using a scenario planning approach. It focuses on identifying driving forces, critical uncertainties, and possible future scenarios in the zakat industry, and formulating adaptive strategies. Research Methodology: A qualitative descriptive design was employed, with data collected through in-depth interviews involving internal and external stakeholders, supported by secondary data. PESTEL and Porter’s Five Forces analyses identified 29 driving forces, which were assessed using an impact/uncertainty matrix and developed into a 2×2 scenario matrix, producing four potential future situations. Results: Four scenarios were generated: Jumping Frog, Accelerate to Excellence, The Struggle, and Business as Usual as a reference description of the conditions that need to be considered when dealing with uncertain conditions in the future, so that the institution can determine its strategic direction more optimally. Institutions need to consider the implications and options strategies in each scenario to strengthen the ability of today's institutions to deal with various conditions that will arise in the future. Conclusion: Scenario planning enables Rumah Zakat to anticipate and prepare for various future conditions, reducing risks from environmental uncertainties. Implementing common strategies such as collaborating with government zakat institutions, leveraging CSR funds, fostering talent, digitizing processes, and innovating business models will enhance institutional resilience and competitiveness.. Limitations: The study is limited to a single case, a qualitative data scope, and a small number of expert informants, making generalization cautious. Contribution: This research contributes to strategic management in Islamic philanthropy by demonstrating the practical application of scenario planning for adaptive and sustainable long-term strategy formulation.